Evolution of tidal flats in the Yellow River Qingshuigou sub-delta: spatiotemporal analysis and mechanistic changes (1996-2021) - Cao, Yin; Wang, Qing; Zhan, Chao; Li, Rui; Qian, Zhangfan; Wang, Longsheng; Liu, Xianbin; Zhu, Jun; Shi, Hongyuan; Li, Yan (Frontiers in Marine Science, 2023)
The Yellow River Delta has undergone significant changes, developing a temperate chalk-sand silty coast with expansive and level tidal flats. However, the area is currently facing the threat of erosion due to coastal area construction, decreased river sediment discharge into the sea, and intensified marine hydrodynamic forces. Remote sensing technology has important applications in spatial and temporal monitoring of tidal flats. This study employs tidal data to establish the threshold range for the extraction of tidal flats in the Yellow River Qingshuigou sub-delta, using the water frequency method based on the image element proposed by previous authors. The study successfully identifies and analyzes the range of tidal flats, and further delves into their evolutionary process and underlying mechanisms. The study concludes that the area of tidal flats has shown a decreasing trend and was divided into a “rapid decline phase” and an “overall stabilization phase” with 2006 as the boundary. The spatial and temporal evolution of tidal flats is primarily influenced by three main factors: river sediment discharges, marine hydrodynamic forces, and anthropogenic reclamation activities. Specifically, the river sediment discharges and marine hydrodynamic forces impact the extent of tidal flats by modifying the boundary conditions, primarily at the sea boundary. Reclamation activities have a direct and rapid effect on the extent of tidal flats, primarily at the land boundary. In this study, we determined the contribution of three factors to the spatial and temporal evolution of tidal flats in different periods. During the two phases of the tidal flats’ spatial and temporal evolution in the Yellow River Qingshuigou sub-delta, the driving mechanisms were identified as “reclamation - marine hydrodynamic forces - river sediment discharges” and “marine hydrodynamic forces - river sediment discharges - reclamation”.